Relationship between recurrent colorectal cancer and EGFR inhibitor-induced dermatological side effects: a focus on paronychia - Esmez, Omer; Esmez, Merve Yildiz; Deniz, Gulnihal (Bmj Publishing Group, 2026)
This case describes a woman in her mid-40s with recurrent colorectal cancer who developed severe dermatologic toxicity during panitumumab-based therapy. Three months after treatment initiation, she developed a diffuse acneiform eruption, pronounced xerosis and painful periungual inflammation with exuberant granulation tissue consistent with epidermal growth factor receptor (EGFR)-inhibitor-induced paronychia. Multidisciplinary, guideline-concordant supportive care (including prompt topical measures and short-course systemic therapy) achieved symptom control and allowed continuation of anticancer treatment. This report underscores the importance of early recognition and structured management of EGFR-inhibitor toxicities to prevent treatment disruption and preserve quality of life.
Keywords: Cancer; Dermatology; Colon cancer; Orthopaedics; Unwanted effects / adverse reactions